Investigasi Pengaruh Sosial Media Marketing dan Brand Awereness terhadap Purchase Decision Produk Indihome pada Wilayah Telkom Bengkulu - Ratnawia Ratnawia; Ilma Mufidah; Husni Amani (STKIP PGRI SITUBONDO, 2022)
The impact arising from the expansion of the internet network is the need for internet all the time. Many companies that provide internet services to users which is PT. Telkom Indonesia with its IndiHome product. IndiHome products in Bengkulu Province have a very low installation value through non-sales compared to other areas in Sumatra. Researchers will conduct basic research on digital marketing through social media and increasing brand awareness which will affect the increase in sales of IndiHome products through non-sales. This research has 3 variables, namely social media marketing, brand awareness and purchase decision. This research has conducted a survey to 164 people of Bengkulu Province with 18 research indicators. Calculation of survey results using the PLS method with the smartpls application. The results of the research are Social media marketing and brand awareness affect the purchase decision coefficient of determination of 0.771 or 77.1%. While the remaining 22.9% (100-77.1) was contributed by variables outside the study.